Research on the relationship between sports scientific training and athletes'mental health - Han, F. (Revista Brasileira de Medicina do Esporte, 2021)
Introduction: Regarding sports mental fatigue research, foreign countries mainly discuss the theoretical model of mental exhaustion. Among them, Silva's theoretical model believes that sports mental fatigue is a negative training stress response. Domestic research mainly analyzes and discusses the concept, causes, and monitoring of mental fatigue. Objective: This study explores the relationship between sports fatigue and mental health of elite athletes through investigation and analysis; analyzes whether social support plays a moderating role in training stress and how aspect support plays an important role. Methods: Based on the stress theory and the negative training stress response model theory, the paper used the Mental Health Inventory (PHI), Athlete Exercise Fatigue Questionnaire, Social Support Rating Scale, and Perceived Social Support Scale to analyze 163 outstanding athletes above the first level. Carry out investigation, use SPSS10.0 software to carry out reliability analysis, Pearson correlation analysis, and multiple linear stepwise regression analysis. Results: The mental health level of elite athletes is closely related to the degree of sports fatigue, and the correlation coefficients between most factors have reached a significant level. The physical (emotional) exhaustion in sports fatigue is an important predictor of the mental health of elite athletes; age, sports grade, economic conditions, perceived family support, and mental health are important predictors of sports fatigue for elite athletes; social support is an important external "buffer" in the process of training stress, in which family support and emotional support play a major regulatory role. Conclusions: The research results can provide references for maintaining and promoting athletes` physical and mental health, provide some useful references for mental health education of sports teams, and provide empirical data for sports psychology and health psychology.